Iron and chromium co-doped cobalt phosphide porous nanosheets as robust bifunctional electrocatalyst for efficient water splitting. (24th November 2021) - Sun, Shichao; Wang, Zhihong; Meng, Suci; Yu, Rui; Jiang, Deli; Chen, Min
Abstract: It is still a huge challenge to develop highly efficient and low-cost non-precious metal-based electrocatalysts for overall water splitting in alkaline electrolytes. Herein, Cr and Fe co-doped CoP porous mesh nanosheets (Mesh-CrFe-CoP NSs) were synthesized through hydrolysis reaction, ion exchange etching and subsequent low-temperature phosphating process. The Mesh-CrFe-CoP NSs provides overpotentials at a current density of 10 mA cm −2 under alkaline electrolyte of 103.7 mV and 256.4 mV for HER and OER, respectively. Furthermore, when using Mesh-CrFe-CoP NSs as anode and cathode, the water splitting system could afford a current density of 10 mA cm –2 at 1.55 V, which is better than an electrolytic cell composed of 20% Pt/C and RuO2 . The excellent electrocatalytic performance of Mesh-CrFe-CoP NSs is attributed to the co-doping and porous nanostructure. Specifically, the Cr and Fe co-doped porous CoP nanosheets electrocatalyst not only provided abundant exposure active sites, accelerated the entry of liquid and the diffusion of gas, but also regulated the electronic environment of active sites, and thus enhanced the electrochemical performance. This work proposes a strategy for the rational design of highly efficient and stable non-precious metal co-doped phosphide electrocatalysts in the of electrochemical water splitting.